Posttraumatic versus Mycotic Dorsalis Pedis Pseudoaneurysm - Lynch, James E.; Winkler, Katrina A.; Xenos, Eleftherios (International Journal of Angiology, 2013)
Reports of dorsalis pedis aneurysms are rare, and there are currently no reports of mycotic dorsalis pedis aneurysms in the literature. Most dorsalis pedis pseudoaneurysms are diagnosed by physical exam and color flow duplex. Surgical treatment includes aneurysm resection with or without reconstruction of the dorsalis pedis artery. We report a dorsalis pedis pseudoaneurysm diagnosed clinically and via duplex ultrasound, treated by excision and ligation of the aneurysm.
Keywords: aneurysm; ultrasound; resection; artery; ligation; excision